PELESTARIAN BAHASA BATAK TOBA DARI TINJAUAN SOSIOLOGI DAN STRUKTUR BAHASA - Tomson Sibarani (Balai Bahasa Sumatera Utara, 2019)
Toba Batak language is one of the local languages in North Sumatra that is used and maintained by a community of native speakers ie Batak Toba or so-called ethnic Batak Toba. Batak Toba. Giles and Ryan (1920) suggests the existence of sociocultural factors determining the basis of how attitudes evolve language and expressed by speakers. The first is the standardization of the language and the second is vitality. Downes (1998: 62) suggests factors that also affect the preservation of language, among others are: family, relationships, communication intensity, activity, desire. Toba Batak speakers region is geographically located in the middle region of North Sumatra province which is in the back of Bukit Barisan located 1o20'-2o4 'north latitude and 98o10'-90o35' east longitude, with a temperature of around 17-29 with an average humidity approximately 85.04%, has a total area of 10605.3 km2 or 1.06053 million hectares including the waters of Lake Toba area of 1102.6 km2 or 110,260 ha. Toba Batak language in its development has suffered a setback on the younger generation both in existing areas as well as urban speakers. This is a concern that the author can adversely impact the development of the Toba Batak language. Toba Batak language teaching is not the maximum and allow the entry of Indonesian and foreign into Toba Batak language is one of the problems faced by Toba Batak language development. The method used in this research is quantitative method using direct interviews and the records tapping method to determine the authenticity of the vocabulary in the language Batak Toba. Speakers and government attention to the preservation of Toba Batak language is now declining and may lead to the extinction of Toba Batak language.